Gain-of-Function Mutations in the Toll-Like Receptor Pathway: TPL2-Mediated ERK1/ERK2 MAPK Activation, a Path to Tumorigenesis in Lymphoid Neoplasms? - Rousseau, Simon; Martel, Guy (Frontiers in Cell and Developmental Biology, 2016)
Lymphoid neoplasms form a family of cancers affecting B-cells, T-cells and NK cells. The Toll-Like Receptor (TLR) signalling adapter molecule MYD88 is the most frequently mutated gene in these neoplasms. This signalling adaptor relays signals from TLRs to downstream effector pathways such as the Nuclear Factor kappa B (NFB) and Mitogen Activated Protein Kinase (MAPK) pathways to regulate innate immune responses (Kawai and Akira, 2010). Gain-of-function mutations such as MYD88[L265P] activate downstream signalling pathways in absence of cognate ligands for TLRs, resulting in increased cellular proliferation and survival. This article reports an analysis of non-synonymous somatic mutations found in the TLR signaling network in lymphoid neoplasms. In accordance with previous reports, mutations map to MYD88 pro-inflammatory signaling and not TRIF-mediated Type I IFN production. Interestingly, the analysis of somatic mutations found downstream of the core TLR-signaling network uncovered a strong association with the ERK1/2 MAPK cascade. In support of this analysis, heterologous expression of MYD88[L265P] in HEK 293 cells led to ERK1/2 MAPK phosphorylation in addition to NFB activation. Moreover, this activation is dependent on the protein kinase Tumour Promoting Locus-2 (TPL-2), activated downstream of the IKK complex. Activation of ERK1/2 would then lead to activation, amongst others, of MYC and hnRNP A1, two proteins previously shown to contribute to tumour formation in lymphoid neoplasms. Taken together, this analysis suggests that TLR-mediated tumorigenesis occurs via the TPL2-mediated ERK1/2 activation. Therefore, the hypothesis proposed is that inhibition of ERK1/2 MAPK activation would prevent tumour growth downstream of MYD88[L265]. It will be interesting to test whether pharmacological inhibitors of this pathway show efficacy in primary tumour cells derived from hematologic malignancies such as Waldenstrom’s Macroglobulinemia, where the majority of the cells carry the MYD88[L265P] mutation.